Developing a Responsible Attitude to Virtual Being - Important as a Pedagogical Problem - Ovkhunov, I. A. (International Journal on Integrated Education, 2023)
In this article, the legal-normative foundations of the introduction of virtual educational technologies in the field of education, the existence of the need for informatization of education and the information environment in higher education institutions, the development of a responsible attitude to the virtual existence is a pressing social issue of the information society. is considered.